Effects of daily consumption of the probiotic Bifidobacterium animalis subsp. lactis CECT 8145 on anthropometric adiposity biomarkers in abdominally obese subjects: a randomized controlled trial - Pedret, Anna (Int J Obes (Lond), 2018)
BACKGROUND: The effects of probiotic Bifidobacterium animalis subsp. lactis CECT 8145 (Ba8145) and those of its heat-killed form (h-k Ba8145) on human anthropometric adiposity biomarkers are unknown. OBJECTIVE: To assess the effect of Ba8145 and h-k Ba8145 ingestion on anthropometric adiposity biomarkers. DESIGN: Randomized, parallel, double-blind, placebo-controlled trial with abdominally obese individuals. Participants (n = 135) consumed 1 capsule/day containing 10(10) colony forming unit (CFU) of Ba8145, 10(10) CFU of h-k Ba8145, or placebo (maltodextrin) for 3 months. RESULTS: Ba8145 ingestion decreased waist circumference, waist circumference/height ratio, and Conicity index (P < 0.05) versus its baseline. Changes versus the placebo group reached significance (P < 0.05) after the h-k Ba8145 treatment. Ba8145 decreased the body mass index compared with baseline and placebo group (P < 0.05). The decrease in visceral fat area after Ba8145 treatments reached significance (P < 0.05) only after h-k Ba8145. When analyses by gender were performed, significance remained only for women. Diastolic blood pressure and HOMA index decreased (P < 0.05) after h-k Ba8145. Gut microbiome analyses showed an increase in Akkermansia spp. after Ba8145 treatment, particularly in the live form, which was inversely related to weight (P = 0.003). CONCLUSIONS: In abdominally obese individuals, consumption of Ba8145, both as viable and mainly as heat-killed cells, improves anthropometric adiposity biomarkers, particularly in women. An increase in the gut Akkermansia genus appears as a possible mechanism involved. Our results support Ba8145 probiotic as a complementary strategy in obesity management.